Responsive Meta-Evaluation: A Participatory Approach to Enhancing Evaluation Quality. (March 2017) - Sturges, Keith M.; Howley, Caitlin
In an era of ever-deepening budget cuts and a concomitant demand for substantiated programs, many organizations have elected to conduct internal program evaluations. Internal evaluations offer advantages (e.g., enhanced evaluator program knowledge and ease of data collection) but may confront important challenges, including credibility threats, conflicts of interest, and power struggles. Thus, demand for third-party meta-evaluation may be on the rise to offset such limitations. Drawing on the example of a moderately large and fairly complex five-year program to build state department of education capacity to implement federal education law, this article explores the development and use of external responsive meta-evaluation (RME) to build evaluator capacity, enhance the evaluation's quality, optimize evaluation use, and minimize conflict. After describing RME, the authors discuss its activities, strengths, and limitations through the case example of the Appalachia Regional Comprehensive Center. The article concludes with recommendations for adapting RME for use in various settings.